Telomerase RNA Component Genetic Variants Interact With the Mediterranean Diet Modifying the Inflammatory Status and its Relationship With Aging: CORDIOPREV Study. (5th October 2016) - Gomez-Delgado, Francisco; Delgado-Lista, Javier; Lopez-Moreno, Javier; Rangel-Zuñiga, Oriol Alberto; Alcala-Diaz, Juan Francisco; Leon-Acuña, Ana; Corina, Andreea; Yubero-Serrano, Elena; Torres-Peña, Jose David; Camargo, Antonio; Garcia-Rios, Antonio; Caballero, Javier; et al.
Abstract: Background: Leukocyte telomere length (LTL) attrition has been associated with age-related diseases. Telomerase RNA Component (TERC) genetic variants have been associated with LTL; whereas fatty acids (FAs) can interact with genetic factors and influence in aging. We explore whether variability at the TERC gene locus interacts with FA profile and two healthy diets (low-fat diet vs Mediterranean diet [MedDiet]) modulating LTL, glucose metabolism, and inflammation status in coronary heart disease (CHD) patients. Methods: Inflammation status (high-sensitivity C-reactive protein [hsCRP], glucose metabolism—glucose, insulin, and glycated hemoglobin [HbA1c], and homeostasis model assessment of insulin resistance [HOMA-IR]), LTL, FAs, and single nucleotide polymorphisms (SNPs) of the TERC gene ( rs12696304, rs16847897, and rs3772190 ) were determined in 1, 002 patients from the CORDIOPREV study (NCT00924937). Results: We report an interaction of the TERC rs12696304 SNP with monounsaturated fatty acid (MUFA) affecting LTL ( p interaction = .01) and hsCRP ( p interaction = .03). Among individuals with MUFA levels above the median, CC individuals showed higher LTL and lower hsCRP than G-allele carriers. Moreover, MedDiet interacted with TERC rs12696304 SNP ( p interaction = .03). Specifically, CC individuals displayed a greater decrease in hsCRP than G-allele carriers. These results were not adjusted for multiple statistical testing and p less than .05 was considered significant. Conclusions: Our findings suggest that the TERC rs12696304 SNP interacts with MUFA improving inflammation status and telomere attrition related with CHD. Moreover, the MedDiet intervention improves the inflammatory profile in CC individuals compared with the G-allele carriers. These interactions could provide a right strategy for personalized nutrition in CHD patients.